Burying Libor - Sven Klingler; Olav Syrstad (Norges Bank, 2019)
We argue that the planned transition toward alternative benchmark rates gives reason to mourn Libor. Guided by a model in which banks and non-banks can lend to each other, subject to realistic regulatory constraints, we show empirically that tighter financial regulation increases interbank rates but lowers broad rates (in which lenders are non-banks) and that all market rates increase with more Treasury bill issuance. Hence, the proportion of non-bank lenders affects the alternative rates, introducing variation in the benchmark that is unrelated to banks' marginal funding costs and creating a basis between regions with interbank rates and broad rates.
hdl:11250/2652687
Keywords: E43; G12; G18; 330; Benchmark rates; financial regulation; Libor; repo rates; collateral